First baby achieved by in vitro fertilization in the Peruvian Amazon - Arroyo Tirado, Raúl (2021)
In Peru, most fertility centers are located in Lima, the capital city of Perú, and in a few main cities on the country’s coast and the Andes. For this reason, many couples in the Amazon are forced to relocate outside their city of residence to start their assisted reproduction treatment, despite the enormous difficulties that this represents for them. In this report, we describe the first baby born by in vitro fertilization (IVF) in the Amazon Region of Peru, where all medical and laboratory assisted reproduction procedures were performed in situ.